Analisis Pengembangan Pariwisata Terkait Mata Pencaharian Ekonomi Kreatif - Ridho Rahmatulloh; Andi Muhammad Fauzan Baso; Muhamad Sobahri; Noerma Kurnia Fajarwati (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
Tourism is a rapidly growing industry globally and is currently a source of employment and livelihood for many people. Tourism development in the region as a development sector cannot be separated from the development of local communities and the construction of supporting facilities. One of the factors in the success of developing a tourist destination is communication. Through communication, opportunities for the popularity of a tourist destination will open up to become more widely known by the wider community. The world of tourism is a sector that can be relied on as a foreign exchange earner so it has a big opportunity to continue to be monitored and developed. This sector is increasingly sought after by the public because tertiary needs are related to the lifestyle patterns of modern society. The higher the economy, education and level of work routine, the greater the demand for travel. The communication revolution that accompanies the tourism industry can be aligned with utilizing promotional strategies through digital means for easy access to fulfill human tertiary needs. The service team targets tourism potential. Rural areas are a source of tourist attraction that utilizes the uniqueness of the region with its natural landscape and original culture. Rural tourism can have an organizational form in the form of a tourist village where all the attractions, amenities and institutions that oversee it come from the initiative of the residents themselves. Rural tourism is a form of memorial tourism, namely activities to remember the past even though in reality, rural tourism tends to divert tourist activities from their daily routine or a kind of escape from the hustle and bustle of urban life.